2019
DOI: 10.1039/c8mt00204e
|View full text |Cite
|
Sign up to set email alerts
|

Rice (Oryza sativa L.) tau class glutathione S-transferase (OsGSTU30) overexpression in Arabidopsis thaliana modulates a regulatory network leading to heavy metal and drought stress tolerance

Abstract: OsGSTU30 increases the abiotic stress tolerance in plants either by its catalytic activity or by modulating the expression of stress responsive genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…). Cr(VI) is a toxic metal and after its entry into plants it initiates a ranges of unfavorable changes (Eleftheriou et al , Pokorska‐Niewiada et al , Sinha et al , Srivastava et al ) and thus, the obtained results are justifiable. We have also noticed that Cr(VI) significantly declined qP and the amount of total chlorophyll (Table , Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…). Cr(VI) is a toxic metal and after its entry into plants it initiates a ranges of unfavorable changes (Eleftheriou et al , Pokorska‐Niewiada et al , Sinha et al , Srivastava et al ) and thus, the obtained results are justifiable. We have also noticed that Cr(VI) significantly declined qP and the amount of total chlorophyll (Table , Fig.…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been reported that Cr(VI) is transported through sulfate transporters in plants (Kaszycki et al 2005, Kim et al 2006. After its entry in the plant system, Cr(VI) creates wide ranges of physiological, biochemical and molecular alterations starting from seed germination to plant death (Eleftheriou et al 2015, Pokorska-Niewiada et al 2018, Sinha et al 2018, Srivastava et al 2019. Thus, continuous investigation of the toxicological impact of Cr(VI) in plants is needed in order to develop strategies for its toxicity mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesize that MT2a may not participate in Cd detoxi cation in grey poplar. GST expression is induced by a wide range of biotic and abiotic stresses, including pathogens, heavy metals, drought, salt or hormones [64][65][66][67]. In Oryza sativa L., the GST proteins might alleviate Cu toxicity by the binding of free Cu 2+ in cells [68], which might be an important mechanism in defence towards heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The high-throughput technologies, next generation sequencing (NGS) i.e., ABI/SOLiD, Roche/454, Illumina/Solexa has made it actually possible to produce genome resources at a sizable level and comparatively low cost [12,13]. The next-generation sequencing have already been e ciently utilized to create largescale transcriptome details in a number of plant species, i.e., Rice [14] Arabidopsis [15,16], wheat [17], barley [18], and maize [19] to identify the candidate genes mechanisms.…”
Section: Introductionmentioning
confidence: 99%